Optimizing Market Reach and Sales Growth for Putri’s Home Cooking Through E-Commerce Integration - Melissa Indah Fianty; Fahmy Rinanda Saputri; Marojahan Tampubolon (I-Com: Indonesian Community Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector have significant potential in the national economy, but they face challenges in adopting digital technology. The main obstacles include limited infrastructure and a lack of understanding in e-commerce management. This study evaluates the implementation of an e-commerce website for Putri’s Home Cooking in Legok, Tangerang, using an innovative approach that combines intensive mentoring and data-driven marketing strategies tailored to the characteristics of the partners. The uniqueness of this program lies in the combination of continuous mentoring and the use of analytical data for more precise marketing decision-making. The methods used include case-based training, the development of user guides, and ongoing evaluation using analytical data to understand customer behavior. The results show that the adoption of the website improves visibility and transaction efficiency while significantly expanding the market. Training helps the partners manage e-commerce independently and optimize digital marketing. The effectiveness evaluation is conducted through partner feedback, site performance analysis, and user engagement. This study demonstrates that digital transformation, based on strategic mentoring and analytics, can sustainably enhance the competitiveness of MSMEs.